Application of Chemometrics for the simultaneous estimation of stigmasterol and β-sitosterol in Manasamitra Vatakam-an ayurvedic herbomineral formulation using HPLC-PDA method - Srikalyani Vemuri, Mohan Kumar Ramasamy, Pandiyan Rajakanu, Rajappan Chandra Satish Kumar, Ilango Kalliappan (Journal of Applied Pharmaceutical Science, 2018)
A new research method has been developed to approach multiresponse optimization for simultaneously optimizing a large number of experimental factors. LC Chromatogram was optimized using Phenomenex RP C18 column (250 x 4.6 mm; 5 μm); mobile phase was surged at isocratic mode with a flow of 1.0 mL/min using methanol and acetonitrile (95:5% v/v) at the detection max of 208 nm with the retention time of 16.3 and 18.1 min for Stigmasterol and β-Sitosterol respectively. Amount of Stigmasterol and β-Sitosterol was quantified and found to be 51.0 and 56.3 μg/ mg respectively. The r2 value of 0.9971 and 0.9960 was found in the linear range of 80-130 μg/mL for Stigmasterol and β-Sitosterol respectively. LOD and LOQ were 6.951, 21.063 μg/mL and 6.048, 18.328 μg/mL for Stigmasterol and β-Sitosterol respectively. The relative standard deviation for the system and the method precision were found to be 0.94%, 0.40% and 1.51%, 1.1% (≤2%) for stigmasterol and β-Sitosterol. Recovery studies were performed and found in the range of 95-105% indicates the accuracy of the developed method. The developed chromatographic method is the first report for the concurrent estimation of Stigmasterol and β-Sitosterol in Manasamitra Vatakam.
Keywords: Chemometrics, Manasamitra vatakam, RP HPLC, Stigmasterol, &beta; -sitosterol.